THE PHILOSOPHY OF PUPPET CHARACTERS BATHARA IN MURWAKALA PLAY FOR THE VALUE OF LEADERSHIP ETHICS - Lestari, Wahyu (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2014)
The study aims to find out the values of leadership ethics in Murwakala play. which is beneficial to society in empowering the existence of the puppet. The position of puppeteers in Central Java is now farther away from the younger generation and society. The preferred method is through an objective method to find out the design of performance according to contemporary tastes, as well as referring to the theory of structuralism in order to uncover the meaning of the textual and contextual performance. Method of observation, interview and documentation are also used, in order to get comprehensive data. The results showed the findings of the ethics of leadership from the teachings of puppet plays Murwakala Asthabrata or eight teachings contained in nature into eight figures in the play, which synergized with the nature of the universe, such as the nature of clouds, rain, water, stars, moon, sun, fire, ocean and earth. The findings are collaborative performances Murwakala played in the new format, according to contemporary tastes, semi-theatrical performances. Another finding is souvenirs designs and culinary business run with team leadership ethics, to enhance the creative industry and economy, establish a relationship with buyers and affiliated institutions, with a supporting program of stakeholders.